Keefektifan tiga jenis perangkap serangga untuk deteksi serangga hama gudang yang menyerang bungkil kopra - Budiman, Diana; Dadang, Dadang; Harahap, Idham Sakti (Jurnal Entomologi Indonesia, 2020)
Stored product insect can cause consumer rejection and economic loss due to quality concerns and  phytosanitary regulation. Insect traps have been regularly used as a control method, however its effectiveness on controlling stored copra meal insect pests is not yet known.This study was carried out to compare the effectiveness of three types of insect traps for detection of insect pests of copra meal.The three types of insect traps were pitfall trap, probe trap, and ultraviolet (UV) light trap (blacklight and LED-light emiting diodes). Research was conducted at Laboratory of Entomology SEAMEO BIOTROP, Bogor and two storage facilities of copra meal in North Sulawesi. Laboratory experiment was conducted using completely randomized design with two factors and four replications. The first factor was the types of insect traps (pitfall trap, probe trap, and probe trap with UV LED) and the second factor was insect species (Lasioderma serricorne (Herbst) and Tribolium castaneum (Fabricius)). The experiment at storage facilities was conducted with nested block design where the insect species trapped were nested in the insect traps. The result of laboratory experiment showed that the probe trap captured more insects (30.4%) significantly higher than pitfall trap (17.1%), however there was no significant difference of number of insects trapped in probe trap with and without UV LED. In addition the probe trap captured more T. castaneum and Tenebroides mauritanicus than other type of insects trap, but probe trap with UV LED was more effective to detect L. serricorne and Necrobia rufipes (Fabricius) in the stored copra meal.